Outbreaks of Foodborne Illness Associated with Common Berries, 1983 through 2019 - Matthew D. Krug; Mary Palumbo; Linda J. Harris; Michelle Danyluk (EDIS)
This publication serves as a reference for anyone concerned about the safety of fresh and frozen berry products. Providing information for those who grow, harvest, process, transport, and serve berries to consumers is important for improving science-based food safety programs for the entire supply chain. Table 1 lists the reported outbreaks of foodborne illness from 1983 through 2019 in which specific berries or mixed berries have been identified as the food vehicle. Table 2 lists the reported outbreaks in which berries were likely the food vehicle. This document is an update to the original 2013 publication. https://edis.ifas.ufl.edu/fs232